1993
DOI: 10.1055/s-0038-1651625
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Antiphospholipid Antibodies and Migraine

Abstract: SummaryWe prospectively studied the prevalence of lupus anticoagulant, anticardiolipin antibodies (aCL) and various haemostatic parameters in 71 patients with migraine and compared the results with a control group of 32 subjects with back pain never having experienced migraine. The patients with migraine were divided into two groups: group I with migraine without (n = 18) and with aura lasting less than 60 min (n = 24) and group II with migraine with prolonged aura or migrainous infarction (complicated migrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
13
1
2
Order By: Relevance
“…Previous studies have reported significant levels of serum APA in migraine patients, indicating a potential role of these factors in prompting attacks [9–11], but this finding has not been confirmed in subsequent studies [38–40]. The finding of serum antiphospholipid antibodies has been identified as a potential risk factor for ischemic stroke in young people [41,15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported significant levels of serum APA in migraine patients, indicating a potential role of these factors in prompting attacks [9–11], but this finding has not been confirmed in subsequent studies [38–40]. The finding of serum antiphospholipid antibodies has been identified as a potential risk factor for ischemic stroke in young people [41,15].…”
Section: Discussionmentioning
confidence: 99%
“…On average, few patients were studied in those works and the results that were obtained vary broadly (from 0% to 37%). No differences were detected between the various subtypes of migraine, nor was any relationship observed between aPL and migraine with aura [10,12,15,17–19].…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is similar to what was found in the population studied by Avcin et al [9], whereas confirmed positivity in the medium-high titers was observed in 12% of our patients. All other published works only involved studies on ACA [8][9][10][11][12][13][14][15][16][17][18][19], while LAC was only mentioned in three older works that described the first case reports or selected neurological patients [7,8,19]. The tests for aPL were repeated over time in only three cases to confirm results [13,18,19] and included comparisons between patients and controls [10][11][12][13]15,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bzw. 104[82] untersuchten Patienten nicht bestätigen. 104[82] untersuchten Patienten nicht bestätigen.…”
unclassified